Pandemic lending: Micro and macro effects of model-based regulation - Franco Fiordelisi; Giulia Fusi; Angela Maddaloni; David Marqués Ibá\~nez (European Central Bank (ECB), 2022)
When the Covid-19 crisis struck, banks using internal-rating based (IRB) models quickly recognized the increase in risk and reduced lending more than banks using a standardized approach. This effect is not driven by borrowers' quality or by banks in countries with credit booms before the pandemic. The higher risk sensitivity of IRB models does not always result in lower credit provision when risk intensifies. Certain features of the IRB models - the use of a downturn Loss Given Default parameter - can increase banks' resilience and preserve their intermediation capacity also during downturns. Affected borrowers were not able to fully insulate and decreased corporate investments.
Keywords: G21; G28; 330; Model-based regulation; Banks; Supervision; Lending; Covid-19